Periodontal health, nutrition and anthropometry in professional footballers: A preliminary study - Botelho, J.; Vicente, F.; Dias, L.; Júdice, A.; Pereira, P.; Proença, L.; Machado, V.; Chambrone, L.; Mendes, J. J. (Nutrients, 2021)
Poor oral health in elite sport is a pressing issue, however little is known about the periodontal status of professional footballers. The aim of this study was to examine the prevalence of periodontitis in a group of professional footballers and its association with nutritional parameters and self-report non-traumatic injuries. Additionally, we assessed its association with anthropometric, dietary inflammatory load and self-reported muscular and/or articular injuries. Twenty-two professional footballers were evaluated at the beginning of the 2020-2021 season via full-mouth periodontal inspection, anthropometric measurements and the application of the dietary inflammatory index through a food intake measurement of 24 h dietary recall on two different days. Self-reporting non-traumatic muscular and articular injuries for the past 6 months were recorded from each athlete. Then we compared clinical measurements according to the periodontal status and we correlated age, periodontal and nutritional parameters. Overall, the prevalence of periodontitis was 40.9% and peri-implantitis was also observed. No significant differences were found regarding age or nutritional parameters according to the periodontal status. More non-traumatic muscular events in the past 6 months were found in the periodontitis group (55.6% vs. 38.4%), although the difference was non-significant. Both clinical attachment loss, periodontal pocket depth and the periodontal epithelial surface area revealed a significant moderate correlation with the percentage of fat mass, muscle mass, muscle mass index and total adipose folds. This group of professional footballers showed an alarming prevalence of periodontitis. Further studies shall examine whether periodontitis and periodontal treatment impact the performance of this group of athletes.